Revisiting the ‘invisible hand’ hypothesis: a comparative study between Bulgaria and Germany - Nadezhda GESHEVA; Aleksandar VASILEV (Eastern Journal of European Studies, 2017)
This paper examines Adam Smith’s concept of an Invisible Hand of the market in light of the underlying assumptions for the theory to hold. Furthermore, the study focuses on Total Factor Productivity as a measure of efficiency of resource allocation, and employs growth accounting in Bulgaria relative to a frontier country (Germany), and tries to explain the Total Factor Productivity gap with the difference in the quality of institutions and economic freedom performance (where the latter is based on the Freedom Index Indicators). Satisfactory results have been obtained, favouring the hypothesis that freer markets perform better and a “catching up” effect of Bulgaria’s Total Factor Productivity levels towards those of Germany has been observed. Finally, the study provides policy recommendations facilitating the Invisible Hand Process in Bulgaria for a more rapid convergence towards Germany’s productivity levels.